The Association between Blood Glucose Control Measured with Serum Hna1c Level with Peroneal Motor Nerve Conduction Velocity in Patients with Type 2 Diabetes Mellitus with Polyneuropathy (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and Objective. The poor control of blood glucose levels in patients with diabetes mellitus is a major risk factor from various complications of diabetes mellitus, such as polyneuropathy. One of the nerves that are often affected in the case of diabetic neuropathy is the peroneal nerve. This study aimed to determine the association between blood glucose level control measured with serum hemoglobin A1c (HBA1c) levels with peroneal motor nerve conduction velocity in type 2 diabetes mellitus patients with polyneuropathy. Methods. The study was conducted on diabetic neuropathy patients who fulfilled inclusion and exclusion criteria in neurology unit and diabetes unit Dr. Soetomo General Hospital Surabaya on a consecutive basis from February to July 2013. The serum HbA1c level and nerve conduction velocity in peroneal motor nerve were examined; then, the results were grouped into two groups which were serum HbA1c
Keywords: : polyneuropathy, HbA1c, nerve conduction velocity, diabetes mellitus